2014
DOI: 10.1007/s10856-014-5214-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fully aligned bioactive electrospun fibers for “in vitro” nerve guidance

Abstract: Complex architecture of natural tissues such as nerves requires the use of multifunctional scaffolds with peculiar topological and biochemical signals able to address cell behavior towards specific events at the cellular (microscale) and macromolecular (nanoscale) level. In this context, the electrospinning technique is useful to generate fiber assemblies having peculiar fiber diameters at the nanoscale and patterned by unidirectional ways, to facilitate neurite extension via contact guidance. Following a bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…58 An excellent review by Biazar et al discusses various types of biologic nerve conduits and synthetic nerve guides. 59 Cirillo et al 60 …”
Section: Nerve Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…58 An excellent review by Biazar et al discusses various types of biologic nerve conduits and synthetic nerve guides. 59 Cirillo et al 60 …”
Section: Nerve Regenerationmentioning
confidence: 99%
“…These fully aligned nanofibers act as a topological cue for neurite growth, thereby improving nerve regeneration. 60 The in vivo studies of intraluminal nanofibrous nerve guides for nerve injury repair have shown considerable improvement in nerve growth potential. The conduits are coated with laminin and nerve growth factors for this purpose.…”
mentioning
confidence: 99%
“…The use of fibrous proteins allows reproducing during the regeneration processes the pattern of chemical and morphological cues typically exerted by natural collagen in vivo at the site of injury. 9,10 In this context, alternative proteins have been more recently tested alone or in combination with other polymers to design protein-based fibrous scaffolds with peculiar functionalities for tissue engineering applications. In particular, the use of collagen for the fabrication of nanofibers via electrospinning technique has been long time considered an effective strategy to design fiber scaffolds with different, morphology, structural arrangement, surface roughness, and porosity, by an accurate control of process parameters and solution properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these limitations, collagen or its denatured protein-that is, gelatin-have been used in the crosslinking form, 2 or in combination with biodegradable polymers including poly(lactic acid), 3,4 poly(glycolic acid) 5 and their copolymer poly(lactic-co-glycolic acid) (PLGA), 6 and poly(ε-caprolactone) (PCL) 7,8 to improve the in vitro and in vivo biomechanical stability. 9,10 In this context, alternative proteins have been more recently tested alone or in combination with other polymers to design protein-based fibrous scaffolds with peculiar functionalities for tissue engineering applications. For instance, silk-based materials have been largely considered for their capability to improve proliferation also supporting mechanical properties to the scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…AFM morphological images of ( A ) solvent casting poly(ε-caprolactone) (PCL) films (scan area 50 × 50 µm 2 ) [53]: ( B ) PCL-Gel electrospun membrane (scan area 20 × 20 µm 2 ) [54]; ( C ) PLGA electrosprayed microparticle (scan area 20 × 20 µm 2 ).…”
Section: Figurementioning
confidence: 99%